Untargeted serum metabolomics reveals potential biomarkers and metabolic pathways associated with esophageal cancer - Yang, Xiao-li; Wang, Peng; Ye, Hua; Jiang, Ming; Su, Yu-bin; Peng, Xuan-xian; Li, Hui; Zhang, Jian-ying (Frontiers in Oncology, 2022)
Metabolomics has been reported as an efficient tool to screen biomarkers that are related to esophageal cancer. However, the metabolic biomarkers identifying malignant degrees and therapeutic efficacy are still largely unknown in the disease. Here, GC-MS based metabolomics was used to understand metabolic alteration in 137 serum specimens from patients with esophageal cancer, which is approximately twice - five folds as many plasma specimens of the previous reports. The elevated amino acid metabolism is in sharp contrast to the reduced carbohydrate as a characteristic feature of esophageal cancer. Comparative metabolomics showed that the most metabolic differences were determined between the early-stage (0-II) and the late-stage (III and IV) among the 0-IV stages of esophageal cancer and between patients who received treatment and those who did not receive treatment. Glycine, serine and threonine metabolism and glycine were identified as the potentially overlapped metabolic pathway and metabolite, respectively, in both disease progress and treatment effect. Glycine, fructose, ornithine, and threonine can be a potential array for evaluation of disease prognosis and therapy in esophageal cancer. These results highlight the way in identifying previously unknown biomarkers related to esophageal cancer by metabolomics approach.